2020
DOI: 10.1097/md.0000000000022181
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of taking traditional Chinese medicine orally in renal interstitial fibrosis

Abstract: Background: By now, the incidence of chronic kidney disease (CKD) is increasing. The development of various CKD is attributed to the continuous aggravation of renal interstitial fibrosis (RIF) in the process of end-stage renal disease (ESRD). Oral treatment of traditional Chinese medicine (TCM) is one of the therapies for RIF. Randomized controlled trials (RCTs) of TCM treatment RIF have been reported, but its effectiveness and safety have yet been systematically investigated. Therefore, through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Traditional Chinese medicine has the advantages of small toxic side effects and multi-target and multi-pathway. It has been clinically proven that traditional Chinese medicine has good efficacy in improving RF and delaying slow renal failure, [7] so the development of new traditional Chinese medicine preparations is extremely valuable.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese medicine has the advantages of small toxic side effects and multi-target and multi-pathway. It has been clinically proven that traditional Chinese medicine has good efficacy in improving RF and delaying slow renal failure, [7] so the development of new traditional Chinese medicine preparations is extremely valuable.…”
Section: Introductionmentioning
confidence: 99%
“… 15 A meta-analysis suggested that the combination of TCM and Western medicine was much more effective in treating RF than Western medicine alone. 16 YiShen HuoXue decoction (YSHXD) is composed of Rhei Radix et Rhizoma (Da Huang, DH), Angelica sinensis Radix (Dang Gui, DG), Achyranthes bidentata Radix (Niu Xi, NX), Salviae Miltiorrhizae Radix et Rhizoma (Dan Shen, DS), Notoginseng Radix et Rhizoma (San Qi, SQ), Carthami Flos (Hong Hua, HH) and Astragali Radix (Huang Qi, HQ). Modern pharmacological studies have confirmed that DH, DS, HQ, DG, SQ, NX, HH and their components can inhibit RF and inflammatory responses and promote kidney repair.…”
Section: Introductionmentioning
confidence: 99%
“…After years of research, the advantages of TCM in improving RF and delaying chronic renal failure (CRF) have been gradually proved. 5 Shendi Bushen capsule (SDBS) is a Chinese patent medicine derived from the classic prescription of traditional Chinese medicine. It is suitable for the decompensation period and renal failure period of CRF in the middle and late stages of RF.…”
Section: Introductionmentioning
confidence: 99%